Analysis and Reduction of the Sloshing Phenomena Due To Sudden Movement of Spray Mixture Tanker - Micheli, G. B. [UNESP]; Fogal, M. L.F. [UNESP]; Scalon, V. L. [UNESP]; Padilha, A. [UNESP]; Ismail, K. A.R. (Academic World Research, 2022)
The sloshing phenomenon occurs in partially filled tankers due to sudden movement can affect the tank structure integrity and impair the dynamic stability of the tanker. The effects of sloshing phenomena in a spray mixture tank due to acceleration or deceleration of the agricultural vehicle is investigated under three filling levels of 25%, 50%, and 75%. The pressure time distributions on the tank wall were evaluated by using a multiphase transient model (water and air as an ideal gas) and a free surface flow in a homogeneous model. It was possible to verify the wave behavior of sloshing. The condition of 75% tank filling volume generated the highest pressure on the tank wall. The effectiveness of two types of vertical baffles in suppressing pressure was numerically investigated. Shear stress on the tank bottom wall under these proposed arrangements was analyzed by steady-state models and mechanical agitation, considering a filled tank. The proposed solution based on two partial vertical baffles and a central gap was the most effective. It promotes the higher reduction of wall impact pressure and other sloshing instabilities and maintains similar results of mixture agitation of the tank without baffles
Keywords: Cfd analysis; Impact pressure; Sloshing; Spray tank; Tank with baffles